1982
DOI: 10.1073/pnas.79.22.6890
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic drugs are inhibitors of phosphatidylcholine synthesis.

Abstract: Clofibric acid (CPIB) and several other systemic hypolipidemic drugs are shown to block phosphatidylcholine synthesis by inhibiting cholinephosphotransferase (ChoPTase; CDPcholine:1,2-diacylglycerol cholinephosphotransferase, EC 2.7.8.2) and particularly lysolecithin acyltransferase (LLAcylTase;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 50 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…Control animals were infused with the vehicle solution without the drug. [24]. MDL 29350 completely inhibited the rat microsomal PE N-methyltransferase activity at a concentration of 5 UM (Fig.…”
Section: Resultsmentioning
confidence: 78%
“…Control animals were infused with the vehicle solution without the drug. [24]. MDL 29350 completely inhibited the rat microsomal PE N-methyltransferase activity at a concentration of 5 UM (Fig.…”
Section: Resultsmentioning
confidence: 78%
“…In addition to increases in the content of PtdCho and PtdEth observed for all treatments (Figure 4), our data show that PFDA and PFOA also caused an increase in the mole percentage of PtdCho, while Wy-14,643 increased the percentage of PtdEth (Table 1). Contrary to these findings, Parthasarathy et al (55) have shown that several hypolipidemic drugs, including clofibrate, inhibited PtdCho synthesis in rat liver microsomes. Thorne and co-workers (17) reported that Wy-14,643, DEHP, and clofibrate reduced the synthesis of PtdEth in human fibroblasts; however, all but clofibrate enhanced the synthesis of PtdCho.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies from our laboratory and others have provided evidence that PPs significantly affect liver phospholipid metabolism ( ). The effects of various PPs on the accumulation or degradation of individual phospholipids appear to be varied.…”
Section: Introductionmentioning
confidence: 92%
“…This may account for the increased PC levels in PBC patients [39]. In fact, several hypolipidaemic drugs act by reducing the hepatic synthesis of cholesterol and PC [40] whose serum levels decline concomitantly. Therefore, the increased content of PC in RBC ghosts of PBC patients is most likely the consequence of the increased hepatic cholesterol synthesis.…”
Section: Discussionmentioning
confidence: 99%